POLITIK HUKUM TENTANG PEMBENTUKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 1 TAHUN 2024 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - Rohma, Putri Mawaddah; Artina, Dessy; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
As a rule of law country, of course Indonesia cannot be separated from legal politicsin forming laws and regulations. According to M. Mahfud MD, legal politics is the state'sofficial legal policy regarding laws that will or will not be enforced (making new rules orrepealing old rules) to achieve state goals. In order to create laws that can protect the people,fair treatment, laws that protect every citizen of the nation so that their rights are guaranteed,of course there must be regulations that serve as guidelines in drafting laws and regulations,as basic rules that apply to drafting regulations from the initial process of their formation upto the regulations. is applied to society. Pekanbaru utilizes the potential of the region toproduce regional income or what is usually called Regional Original Income (PAD) whichwill later include the implementation of autonomy as a replacement for decentralization.This research is normative legal research. This is based on library research whichtakes quotations from reading books, or supporting books that are related to the problem to beresearched. Add data sources. Primary, secondary and tertiary data sources arecharacteristic of this research. This research also uses qualitative data analysis and producesdescriptive data.From the results of the research and discussions carried out, several conclusions wereobtained, namely: First, the urgency of forming regional regulations on regional taxes andlevies essentially contains regional policies that are planned to be implemented in order torealize community welfare. Regulations for the formation of regional regulations regardingRegional Taxes and Levies are of course a need for each region to improve the regionaleconomy and improve the welfare of the community. Second, the Basic Framework forLegislative Regulations must actually include three bases or foundations, namelyphilosophical, sociological and juridical foundations. Therefore, the legal politics of formingregional regulations on regional taxes and levies is ideal, if the regional regulations onregional taxes and levies are in accordance with the nature of the formation of regionalregulations, in accordance with the hierarchy of statutory regulations in Indonesia, inaccordance with the principles of formation and material principles. content of statutoryregulations.Keywords: PAD – Regional Taxes and Levies – Regional Government